Dexamethasone attenuates interferon-related cytokine hyperresponsiveness in COVID-19 patients - Engel, Job J.; van der Made, Caspar I.; Keur, Nick; Setiabudiawan, Todia; Röring, Rutger J.; Damoraki, Georgia; Dijkstra, Helga; Lemmers, Heidi; Ioannou, Sofia; Poulakou, Garyfallia; van der Meer, Jos W. M.; Giamarellos-Bourboulis, Evangelos J.; et al. (Frontiers in Immunology, 2023)
Background: Dexamethasone improves the survival of COVID-19 patients in need of supplemental oxygen therapy. Although its broad immunosuppressive effects are well-described, the immunological mechanisms modulated by dexamethasone in patients hospitalized with COVID-19 remain to be elucidated. Objective: We combined functional immunological assays and an omics-based approach to investigate the in vitro and in vivo effects of dexamethasone in the plasma and peripheral blood mononuclear cells (PBMCs) of COVID-19 patients. Methods: Hospitalized COVID-19 patients eligible for dexamethasone therapy were recruited from the general care ward between February and July, 2021. Whole blood transcriptomic and targeted plasma proteomic analyses were performed before and after starting dexamethasone treatment. PBMCs were isolated from healthy individuals and COVID-19 patients and stimulated with inactivated SARS-CoV-2 ex vivo in the presence or absence of dexamethasone and transcriptome and cytokine responses were assessed. Results: Dexamethasone efficiently inhibited SARS-CoV-2-induced in vitro expression of chemokines and cytokines in PBMCs at the transcriptional and protein level. Dexamethasone treatment in COVID-19 patients resulted in down-regulation of genes related to type I and II interferon (IFN) signaling in whole blood immune cells. In addition, dexamethasone attenuated circulating concentrations of secreted interferon-stimulating gene 15 (ISG15) and pro-inflammatory cytokines and chemokines correlating with disease severity and lethal outcomes, such as tumor necrosis factor (TNF), interleukin-6 (IL-6), chemokine ligand 2 (CCL2), C-X-C motif ligand 8 (CXCL8), and C-X-C motif chemokine ligand 10 (CXCL10). In PBMCs from COVID-19 patients that were stimulated ex vivo with multiple pathogens or Toll-like receptor (TLR) ligands, dexamethasone efficiently inhibited cytokine responses. Conclusions: We describe the anti-inflammatory impact of dexamethasone on the pathways contributing to cytokine hyperresponsiveness observed in severe manifestations of COVID-19, including type I/II IFN signaling. Dexamethasone could have adverse effects in COVID-19 patients with mild symptoms by inhibiting IFN responses in early stages of the disease, whereas it exhibits beneficial effects in patients with severe clinical phenotypes by efficiently diminishing cytokine hyperresponsiveness.